Exploring the Paradox of Islamic Boarding School Digital Marketing between the Values of Politeness and the Demands of Social Media Algorithms - Rifka Jannatul Firdausiyah; Muhammad Durrin Ni'am; Ittaqillah Haitsuma Kunta; Siti Nur Aviatun; Moh. Kamil; Mona Novita; Abd. Muis (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to understand how Islamic boarding schools (pesantren) manage the paradox between the value of politeness and the demands of social media algorithms in digital marketing practices. This phenomenon is crucial because Islamic boarding schools are faced with the need to remain relevant in the digital space without losing their foundational values. A qualitative approach was used, with a case study design at the Kwagean Islamic Boarding School in Kediri. Data were collected through direct observation and in-depth interviews with administrators, the media team, and students involved in content production. Data were then analyzed step by step to identify emerging patterns and meanings. The results show that Islamic boarding schools engage in a continuous negotiation process between maintaining politeness and adapting to the logic of the algorithm. Communication styles are made lighter and more adaptive, while remaining within the boundaries of maintained values. On the other hand, algorithms also influence content production patterns, particularly in the tendency to repeat formats deemed effective. This condition creates a hybrid communication identity, where depth of substance is maintained while presented in a simpler manner. These findings illustrate that digital adaptation does not always lead to a loss of values, but can instead provide a space for formulating new, more contextual forms of communication. This study is expected to enrich the discourse on religious digital communication and serve as a practical reference for Islamic boarding schools in managing media wisely amidst the pressures of digital systems.